STRATEGI BERTAHAN HIDUP PETANI PADI SAWAH TADAH HUJAN PADA MUSIM KEMARAU DI DESA CILEBAK - Putri, Kartika Sari (Pekerjaan Sosial, 2023)
Rainfed lowland rice farmers depend their livelihoods on the lowland rice harvest and often experience losses. This is because many farmers speculate or have their chance to plant rice during the dry season. The problems faced by farmers in Cilebak Village are related to agricultural processes that are influenced by dry season conditions and crop failure. Efforts are made by managing family finances, storing rice reserves, managing agricultural patterns, doing other work, and accessing the source system. This research was conducted using qualitative methods with descriptive research type. In-depth interviews were conducted with 13 informants who were selected through purposive sampling technique.